Innovations in Medical Education During the COVID-19 Era and Beyond: Medical Students' Perspectives on the Transformation of Real Public Health Visits Into Virtual Format - Alzayani, Salman; Alsayyad, Adel; Al-Roomi, Khaldoon; Almarabheh, Amer (Frontiers in Public Health, 2022)
Background At the College of Medicine and Medical Sciences, Arabian Gulf University, Bahrain, the Public Health Program comprises of two core components, namely lectures and field visits (Consumer Products Safety, Communicable Diseases Control and Food Safety). Digital transformation has innovated the medical educational activities during the COVID-19 pandemic where the real public health field visits were transformed into virtual format. This study aims to examine the potential effect of converting the real public health field visits program into a virtual format during the COVID-19 pandemic. Methods All medical students who have submitted online feedback evaluation forms upon completing the Public Health Program in the academic years 2019-2020 (180 students; before COVID-19 pandemic) and 2020-2021 (167 students; during the COVID-19 pandemic) were included in the study, a total sample size of 347 responses. Independent sample t test was employed to compare students’ feedback on Public Health Program before and during the COVID-19 pandemic while Pearson chi-square test was used for categorical data. A p-value of less than 0.05 was considered as statistically significant. Results The mean score of students’ satisfaction from the virtual program during the COVID-19 pandemic towards the Consumer Products Safety and Food Safety field visits were significantly higher than that for students before the COVID-19 pandemic (the real field visits). However, there was no observed statistically significant difference for the Communicable Diseases Control visit. In addition, no significant differences were detected between the mean responses of male and female students towards all field visits, whether the feedback was provided before or during the COVID-19 pandemic. Conclusion Transformation of real public health field visits into virtual format is acceptable and applicable during the COVID-19 era and maybe beyond.